(untitled) (Research, Society and Development, 2020)
Improvement in livelihood capitals of vulnerable women farmers has been a concern in the developing countries. Governments around the world particularly in the developing countries try various policies and models to enhance the productivity of these vulnerable women farmers, they do this to protect them against shocks and loses considering that rural food production contribute significantly to national food security. Such is the case in Nigeria, where Adopted Village Model (AVM) was initiated in 2009. The objective of the study includes but not limited to protect, improve and sustain food production in Nigeria through capacitating the rural women rice farmers. AVM was initiated and women farmers where provided information, farm equipment, training, seedlings and subsidized fertilizers. Structured questionnaires and interviews were the basic instruments applied in the data collection. The methodology was guided by sustainable livelihood framework theories. Structured questionnaire was used to extract desired information from the women farmers. The data was analysed with spss version 25, interpreted and presented for public consumption. The study found that AVM was introduced to the women farmers at the right time when yield and livelihood capitals of the rice women farmers where very low. Keywords: Livelihood; Rice; Women farmers; Model; Agriculture